2023
DOI: 10.1038/s41598-023-29743-1
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes prevalence, awareness, and risk factors in rural Mali: a cross-sectional study

Abstract: Diabetes is currently a crisis in sub-Saharan West Africa (SSWA) with dramatic implications for public health and national budgets prioritizing infectious diseases. There is limited recent literature about the prevalence, awareness, and risk factors for type 2 diabetes (T2D) in rural parts of SSWA. This study characterized T2D prevalence and risk factors for the rural Malian community of Nièna, which is situated in Mali’s second-largest province of Sikasso. Between December 2020 and July 2021, a cross-sectiona… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The average age of patients was 35 years, with extremes of 5 and 68 years. The most represented age group was [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], making up 48.33% of the cohort. This average age was lower than that reported in studies conducted by Ben Salem et al in Tunisia in 2020 (45 years old) [11] or in a study carried out in a military hospital in Morocco (44 years old) [12], with a standard deviation of 16 and 15 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average age of patients was 35 years, with extremes of 5 and 68 years. The most represented age group was [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], making up 48.33% of the cohort. This average age was lower than that reported in studies conducted by Ben Salem et al in Tunisia in 2020 (45 years old) [11] or in a study carried out in a military hospital in Morocco (44 years old) [12], with a standard deviation of 16 and 15 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that its overall prevalence was 7.5%, and risk factors were age, family history of diabetes, hypertension, waist circumference, and fetal macrosomia. Notably, 61.3% of type 2 diabetic subjects were unaware of their diabetic status before the study [32]. Recently, a systematic review and meta-analysis has found that the overall prevalence of both overweight and obesity was 61.4% amongst type 2 diabetic African patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that 79% - 100% of T2D subjects were initially diagnosed during cross-sectional surveys [ 33 ]. In one of our earlier studies, a majority (62.5%) of subjects diagnosed with T2D were unaware of their diabetic status [ 34 ]. These results suggest that carrying out field studies are beneficial beyond the research implications.…”
Section: Discussionmentioning
confidence: 99%
“…In people with T2DM, 90% are overweight or obese. DM prevalence has risen faster in low-and middle-income countries than in high-income countries[13]. The highest prevalence rates are currently in the Eastern Mediterranean and Middle East with North and South America close behind.…”
mentioning
confidence: 99%